Lesions of the lateral hypothalamus impair pilocarpine-induced salivation in rats - Renzi, Antonio [UNESP]; De Luca, L. A.; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2002)
In the present study we investigated the effects of electrolytic lesions of the lateral hypothalamus (LH) in the salivation induced by intracerebroventricular (i.c.v.) or intraperitoneal (i.p.) injection of the cholinergic agonist pilocarpine. Rats with sham or LH lesions and stainless steel cannulas implanted into the lateral ventricle (LV) were used. In rats anesthetized with urethane (1.25 mg/kg of body weight) saliva was collected using pre-weighed cotton balls inserted in the animal mouth during a period of 7 min following i.c.v. or i.p. injection of pilocarpine. Injection of pilocarpine (1 mg/kg of body weight) i.p. in sham-operated rats (6 h, 2, 7, and 15 days after the surgery) induced salivation (497+/-24, 452+/-26, 476+/-30, and 560+/-75 mg/7 min, respectively). The effects of i.p. pilocarpine was reduced 6 h, 2 and 7 days after LH lesions (162+/-37, 190+/-32, and 229+/-27mg/7 min, respectively), not 15 days after LH lesions (416+/-89mg/7 min). Injection of pilocarpine (120 mug/mul) i.c.v., in sham-operated rats (6 h, 2, 7, and 15 days after the surgery) also produced salivation (473 20, 382 16, 396 14, and 427 47 mg/7 min, respectively). The salivation induced by i.c.v. pilocarpine was also reduced 6 h, 2 and 7 days after LH lesions (243+/-19, 278+/-24, and 295+/-27 mg/7 min, respectively), not 15 days after LH lesions (385 48 mg/7 min). The present results show the participation of the LH in the salivation induced by central or peripheral injection of pilocarpine in rats, reinforcing the involvement of central mechanisms on pilocarpine-induced salivation. (C) 2002 Elsevier B.V. All rights reserved.
Keywords: salivary glands; salivary secretion; cholinergic receptors; xerostomia; cholinergic agonist